Diagnostic Performance of Fecal pks+ Escherichia coli for Detecting Neoplastic Colorectal Lesions in Suspected Colorectal Cancer Patients - Anton Sumarpo; Ida Parwati; Fajar Wasilah; Didik Setyo Heriyanto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2026)
Genotoxin-producing pks+ Escherichia coli is implicated in the pathogenesis of colorectal cancer (CRC). This study was designed to evaluate the diagnostic performance of fecal pks+ E. coli as a non-invasive biomarker for CRC screening. In this cross-sectional study, fecal samples from 70 patients with suspected CRC were analyzed by quantitative polymerase chain reaction (qPCR) to detect the presence of pks+ E. coli. The diagnostic accuracy was assessed against colonoscopy and histopathology findings. Against histopathology as the gold standard, fecal pks+ E. coli detected neoplastic lesions with a sensitivity of 70.59% and a specificity of 65.22%. Notably, the relative gene copy number of pks+ E. coli was significantly higher in patients with neoplastic lesions compared to those with non-neoplastic findings. Fecal testing for pks+ E. coli demonstrates potential as a non-invasive biomarker for detecting neoplastic colorectal lesions, though further validations are needed.